Two-step pyrolysis of Mn MIL-100 MOF into MnO nanoclusters/carbon and the effect of N-doping. Issue 15 (31st March 2022) - Hu, Yating; Song, Chi; Li, Changjian; Wang, John
Abstract : A two-step pyrolysis of Mn MIL-100 MOF, from which MnO nanoclusters/carbon are obtained, is discovered through various in situ techniques. Abstract : MIL-100 is a class of trimesate MOFs that have been widely studied as candidates for various energy related applications. Understanding a MOF's pyrolysis is important as it determines the different functional materials derived from it. The chemistry and pyrolysis process of Mn MIL-100 are closely examined in this work. A two-step pyrolysis in inert gas is discovered and the products at each step are verified, as well as the phase transition and morphology evolution. The critical conditions to obtain air-stable MnO nanoclusters from this MOF are also identified. In addition, N-doping into this N-free MOF is realized through reacting with dicyandiamide. The effect of N-doping and the correlation between the amount of N doped and the final pyrolysis product are revealed. Through this mechanistic study, a precise control of the nanoscale morphology and composition of the pyrolysis product becomes possible. More specifically, MnO nanoclusters of 4 nm size embedded in a carbon or N-doped carbon matrix could be obtained, as well as Mn2 N x nanoparticles by increasing the level of N-doping.